Correlation in the barbell and lower limb kinematics performance parameters in the snatch lifts: a pilot study - Chuang, M. H.; Chang, L. C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
In our knowledge, there was not a lot of research to understand the relationship of snatch lifting. Therefore, the purpose of this study was to investigate the relationship between the barbell and lower limb kinematics parameters during the second pull of the snatch lifts. There were two digital cameras to record the snatch lifts. The study used the Kwon 3D motion analysis system to obtain the barbell and lower limb kinematics parameters. They study used the Pearson`s product moment correlations to investigate the relationship between the barbell and lower limb kinematics parameters. The results showed the significant relationship between the maximum vertical height of the barbell and the maximum extension angle of the hip joint. It also showed the significant relationship between the maximum extension angle velocity of the knee joint and maximum extension angle of the knee joint. The present study suggests that increasing the muscle quality and power of the lower limbs will increase the maximum vertical velocity of the barbell.